Effectiveness Of Pisbro Cookies In Improving Hemoglobin Levels Among Pregnant Women: A Quasi-Experimental Study - S, Damayanty; Siregar, Erin Padilla; Siagian, Hazizah Sabilah; Kalira, Aurel Sessfy (Journal of Applied Nursing and Health, 2025)
Background: Anemia in pregnancy remains a major cause of maternal complications, low birth weight, and stunting. Although iron–folic acid supplementation is widely implemented, there is a lack of culturally appropriate, food-based interventions using locally available ingredients that can sustainably improve hemoglobin levels in low-resource settings. This gap highlights the need for innovative, community-adaptable nutritional interventions that complement existing programs. The objective was to evaluate the effectiveness of Pisbro cookies (banana–broccoli cookies) in improving hemoglobin levels among pregnant women with anemia. Methods: This study used a quasi-experimental two-group pretest–posttest design and followed the TREND reporting guideline. A purposive sampling method was used to recruit 40 pregnant women with mild–moderate anemia from the Sentosa Baru Health Centre, Medan. Inclusion criteria included: (1) confirmed anemia based on Hb examination, (2) gestational age 12–36 weeks, (3) willingness to participate for 30 days, (4) adherence to Fe tablet consumption. Exclusion criteria included pregnancy complications, chronic illness, allergies to ingredients, and incomplete follow-up. The intervention group received 5 Pisbro cookies/day for 30 days, while the control group received routine antenatal care without additional intervention. Hemoglobin levels were measured at baseline and after 30 days using a calibrated hemoglobin meter. Data were analyzed using an independent t-test at α = 0.05. Results: The intervention group showed an increase in mean hemoglobin levels from 9.56 ± 0.48 g/dL to 9.79 ± 0.51 g/dL, while the control group decreased from 9.62 ± 0.47 g/dL to 9.40 ± 0.50 g/dL. The difference between groups was statistically significant (p = 0.019), indicating a positive effect of Pisbro cookies on maternal hemoglobin levels. Conclusion: Pisbro cookies were effective in improving hemoglobin levels among pregnant women with anemia. As a low-cost, culturally acceptable food-based intervention using locally available ingredients, Pisbro has potential to complement maternal nutrition programs and support anemia and stunting prevention efforts.